Efforts to Counter Radicalism in Sukabumi Regency High Schools - Imanulyaqin, Muhammad Nur (Universitas Tanjungpura, 2024)
Vulnerability to exposure to radical ideology at the high school age level is increasingly widespread with various strategies that are difficult to detect. Therefore, every effort made to counter radical ideology is very important and valuable. The purpose of writing this article is to describe the counter-radicalism strategies carried out by high schools in Sukabumi district. The approach used in this research is qualitative with a descriptive method. The research was conducted in 5 high schools in 5 parts of Sukabumi Regency. The research was conducted for 6 months, namely from March to August 2023. The data collection techniques used were interviews, observation and documentation studies. The data analysis techniques used are data reduction, data display, and drawing conclusions and verification. Research findings show that there are various efforts made by senior high schools in Sukabumi district, although these efforts are still universal and have not focused on specific strategies to counter radicalism. These efforts include optimizing child-friendly schools, optimizing student activities at school, religious habituation and strengthening, optimizing P5, training and coaching deputy principals for student affairs, counter-radicalism programs from parties outside the school, insertion through learning, and encouraging students. towards activities related to counter radicalism outside of school.